Effect of Behavioral Intention Model-based Education on Decrease the Rate of Caesarean Delivery among Pregnant Women - Kashfi, Seyd Mansor; Khani jeihooni, Ali; Babaei Heydarabadi, Akbar; Ashrafi Hafez, Asghar; Rezaianzadeh, Abbas; Shahidi, Fatemeh (Archives of Advances in Biosciences, 2013)
Caesarean section is considered as a major surgery which is accompanied by several complications. The present study aimed to determine the effect of behavioral intention model-based educational intervention on reducing the caesarean section among pregnant women. The present interventional study was conducted on 100 primiparous women in the third trimester of pregnancy who were covered by the health and treatment centers of Fasa city, placed in Fars province, Iran. The subjects were selected through simple random sampling and divided into an intervention and a control group. After the pre-test, the intervention group underwent exclusive training based on the behavioral intention model. Then, both groups took part in the post-test and the data were analyzed using paired t-test, independent t-test, and chi-square tests. The results of the study revealed a significant difference between the two groups regarding knowledge, evaluation of the outcomes, attitude, and intention (P<0.001). The results of the chi-square test also showed a significant difference between the two groups regarding their performance (P<0.001). According to the results, the present intervention was effective in increasing the pregnant women’s knowledge, evaluation of outcomes, attitude and strengthening their intention as well as performance. Thus, this model and other systematic trainings are suggested to be used for pregnant women in order to decrease the rate of caesarean section.